Destination Image of Tourist: Effect of Travel Motivation and Memorable Tourism Experience - Dani Dagustani; Dwi Kartini; Yevis Marty Oesman; Umi Kaltum (ETIKONOMI, 2018)
The eco-tourism area of the southern coast of West Java is the focus of research since the area is less well known as a tourist destination. Also, there is a reluctance of tourists to visit again, and tourists find ordinary. The purpose of this study is to examine the influence model of travel motivation and impressive tourism experience towards the destination image. The method used is verification analysis by using Structural Equation Model (SEM). The survey conducted on 302 respondents, i.e., tourists who visited the eco-tourism area of the southern coast of West Java. The results showed the motivation of travel and tourism experience significantly influence the image of tourism destinations. Tourism area managers need to design strategies to improve the image of the region by providing tourist stimulation in the form of exciting information and offers eco-tourism products-themed for tourist with a memorable approach to traveling experiences.DOI: 10.15408/etk.v17i2.7211